Solitary nodule on the back: A diagnostic challenge on cytology (Indian Journal of Case Reports, 2020)
Evaluation of a solitary lesion on the back can be a diagnostic challenge on cytology. However, based on the histological examination, differential diagnosis can be narrowed down, but still, sometimes, it becomes difficult to make a definitive diagnosis, even on biopsy findings. In such cases, the role of immunohistochemistry (IHC) becomes important. Herein, we present the case of a 49-year-old female who presented with a solitary nodule on the back, where fine-needle aspiration cytology followed by histology and IHC helped in making a definitive diagnosis of pseudolymphoma (lymphocytoma cutis), thereby differentiating it from lymphoma. This differentiation is crucial for early and accurate diagnosis, treatment, and prognosis of the patient.